PEMBUATAN SMARTCONTRACT APLIKASI FUNDRAISING BERBASIS BLOCKCHAIN - Budianto Budianto; Mumpuni, Retno; Endah Wahanani, Henni (Pusat Riset dan Inovasi Nasional, 2023)
Fundraising activities have become a common method to achieve various objectives, including charitable activities and gathering funds from investors for companies. However, cases of fund misuse often occur, leading to inappropriate use of funds or even unfair loss. Therefore, an innovative approach is needed to enhance trust and transparency in the fundraising process. In this study, the use of smart contracts on a blockchain network will be employed as a solution to ensure the security and integrity of each transaction in fundraising activities. By utilizing smart contracts, all transactions in fundraising activities can be verified by all users on the blockchain network. Transaction data recorded on the blockchain is permanent and tamper-proof, preventing any manipulation or fund misuse. Leveraging smart contracts and blockchain technology, fundraising activities can be conducted more efficiently, transparently, and securely. This approach helps improve trust among involved parties and reduces the risk of fund misuse